Peer Editing in Teaching Writing for EFL Learner - Febianti, Kurnia (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2017)
The objective of study was to find out whether there was any significant different between students’ writing skill who were taught by using peer editing techique to the tenth grade students of SMA Negeri 1 Pagar Alam and those who were not. The population of this reserach was all tenth grader of SMA N Pagar Alam. The total number of sample was 72 students which were divided into experimental class and control class the sample was taken by using purposive sampling.Quasi Expremental design was applied in this research. In collecting the data written test was used. The calculation of the independent sample t-test show that tobt was 4.377 The level of significant of 0,05 in two tailed testing df 70. The critical value of t-table was 2,030. Based on the result, the alternative hypothesis would be accepted and the null hypothesis would be rejected. It meant that tobt higher than ttab. It meant that the application of Peer Editing could increase students’ speaking achievement of eighth grader of SMA Negeri 1 Pagar Alam.